Morphological characterization of advanced pepper lines (Capsicum annuum L.) from central Mexico - González-Pérez, Enrique (2025)
Introduction. Of the five cultivated pepper species, Capsicum annuum L. is the most important worldwide, due to its high demand in the food, medical, and cosmetic industries, among others. Mexico has the greatest diversity of cultivated types, including jalapeño, guajillo, ancho, serrano, and habanero. However, some farmers grow native materials that should be studied and preserved, such as mulato and chilaca. In certain cases, like chilaca, there are no improved commercial cultivars, so producers depend on the seed they produce. Objective. To morphologically characterize advanced lines of different C. annuum types from central Mexico. Materials and methods. The study was conducted during the spring-summer cycles of 2022 and 2023, at the Bajío Experimental Station, located in Celaya, Guanajuato, Mexico. In 32 advanced lines of eight C. annuum types, 42 traits were evaluated based on the guidelines of the International Union for the Protection of New Varieties of Plants and the International Plant Genetic Resources Institute guide. The data obtained were analyzed using descriptive statistics and subjected to cluster and correspondence analysis. Results. Morphological variation showed that fifteen plant, leaf, and fruit traits were crucial to differentiating pepper types and lines. Based on similar traits, the cluster analysis grouped them into five clusters. Groups I and III included three pepper types, and six traits presented the highest positive eigenvectors. Conclusions. The observed diversity revealed determinant morphological characteristics to distinguish peppers types and lines, which must complete their genetic improvement process.